2015
DOI: 10.1038/nmat4451
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for maximizing photovoltage in metal-oxide-protected water-splitting photoanodes

Abstract: Metal oxide protection layers for photoanodes may enable the development of large-scale solar fuel and solar chemical synthesis, but the poor photovoltages often reported so far will severely limit their performance. Here we report a novel observation of photovoltage loss associated with a charge extraction barrier imposed by the protection layer, and, by eliminating it, achieve photovoltages as high as 630 mV, the maximum reported so far for water-splitting silicon photoanodes. The loss mechanism is systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
302
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 239 publications
(312 citation statements)
references
References 42 publications
9
302
1
Order By: Relevance
“…In this particular system, research has shown that the conduction mechanism through the SiO 2 is a tunneling process 5,9 and through TiO 2 films greater than ∼2 nm thickness is bulk, trapmediated conduction. 6,7 In principle, for n number of distinct insulator layers in the stack and k parallel conduction pathways, there are n k permutations of conduction mechanisms. With two pathways and a bilayer insulator (e.g.…”
Section: The Pmentioning
confidence: 99%
See 3 more Smart Citations
“…In this particular system, research has shown that the conduction mechanism through the SiO 2 is a tunneling process 5,9 and through TiO 2 films greater than ∼2 nm thickness is bulk, trapmediated conduction. 6,7 In principle, for n number of distinct insulator layers in the stack and k parallel conduction pathways, there are n k permutations of conduction mechanisms. With two pathways and a bilayer insulator (e.g.…”
Section: The Pmentioning
confidence: 99%
“…Unfortunately, the underlying physical properties that control corrosion stability and photovoltaic efficiency of semiconductors are linked, such that Type 0 structures do not generally achieve stable and efficient solar-driven electrolysis. 5,7 The protection layers discussed herein and reported in the literature have permitted the use of highly efficient photovoltaic materials with enhanced stability that allow for the advancement of solar fuel and solar chemical technology. The simplest thin insulator-protected structure that achieves high efficiencies and stabilities as a photoanode is the nSi/SiO 2 /TiO 2 /Metal device utilizing TiO 2 for protection and the surface metal layer as both an OER catalyst and a contact for the resulting Schottky junction.…”
Section: The Pmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower dielectric constant of SiO2 relative to TiO2 means that any increase in SiO2 thickness will also incur a much greater photovoltage penalty than the same increase in TiO2 thickness. 11 This strong dependence of both photovoltage and series resistance on SiO2 thickness makes reducing SiO2 thickness one of the most effective methods for improving silicon MIS photoanode performance.…”
Section: Introductionmentioning
confidence: 99%